Appendicitis scores may be useful in reducing the costs of treatment for right lower quadrant pain - Kirkil, Cuneyt; Karabulut, Koray; Aygen, Erhan; Ilhan, Yavuz Selim; Yur, Mesut; Binnetoglu, Kenan; Bulbuller, Nurullah (Turkish Assoc Trauma Emergency Surgery, 2013)
BACKGROUND Unnecessary hospital admissions and negative appendectomies increase healthcare costs of patients with right lower quadrant (RLQ) pain. This study aimed to evaluate the impact on the cost of treatment of appendicitis scoring systems. METHODS Charts were reviewed of patients admitted to the general surgery ward of our hospital with RLQ pain within a year. Alvarado and Lintula scores were calculated, and a simulation was performed to determine the treatment charges that would have been generated had the scoring recommendations been used for admission and surgical decision-making. RESULTS Of the 114 admitted patients, 64 (56%) underwent appendectomy. The rate of negative appendectomy was 17.2%. The overall accuracy rates of the Alvarado and Lintula scores for both 'admit' and 'operate' decision-making were 82.7% and 91.9%, respectively (p=0.102). Total charges for the 114 patients were $39,655. If the Alvarado or Lintula score had been used, the total treatment charges would have been $34,087 and $25,772 (p=0.015 and p=0.000), with negative appendectomy rates of 18.5% and 3.6%, respectively. CONCLUSION The implementation of Alvarado and Lintula scores for the decision of hospital admission and appendectomy would have reduced overall treatment charges for acute RLQ pain.
Apandisit skorları, sa? alt kadran a?rısı için tedavi maliyetlerini düşürmede faydalı olabilir
Keywords: Acute appendicitis; Alvarado scores; cost; Lintula scores; score